Effects of multiscale porosity and pore interconnectivity on in vitro and in vivo degradation and biocompatibility of Fe–Mn–Cu scaffolds. Issue 21 (21st May 2021) - Mandal, Santanu; Viraj,; Nandi, Samit Kumar; Roy, Mangal
Abstract : Iron (Fe) based scaffolds are promising candidates as degradable metallic scaffolds. Abstract : Iron (Fe) based scaffolds are promising candidates as degradable metallic scaffolds. High strength and ability to control the degradation with tailormade composition and porosity are specific advantages of these scaffolds. In this research work, iron–manganese–copper (Fe–Mn–Cu) based scaffolds, with multiscale porosity, are developed through a powder metallurgy route using naphthalene as a spacer material. The porosity in the scaffolds ranged from 42–76%, where the majority of the macro-pores (≥20 μm) form an interconnected channel network. XRD analysis confirms the presence of MRI compatible and antiferromagnetic austenite as a major phase in all the scaffolds. The developed scaffolds in this study have a minimum ultimate compressive strength of 7.21 MPa (for 30Naph), which lies within the range of the human cancellous bone UCS (2–12 MPa). The degradation rates of the scaffolds are determined from static immersion tests, where the scaffold with the highest porosity (76%) shows a highest degradation rate of 2.71 mmpy when immersed in Hank's balanced salt solution (HBSS) at 37 °C for 30 days. The increased degradation rate of the scaffolds has no cytotoxic effects on MG63 cells as studied by alamar blue assay and live/dead imaging. When implanted in a rabbit femur, the scaffold with higher porosity showed enhanced osteogenesis, as evident through micro-CT and histological analysis. It is hypothesized that the presence of multiscale porosity with a high degree of interconnectivity facilitated better bone regeneration within and around the Fe–Mn–Cu scaffolds.